2016
DOI: 10.4168/aair.2016.8.6.499
|View full text |Cite|
|
Sign up to set email alerts
|

Factors Affecting Recovery Time of Pulmonary Function in Hospitalized Patients With Acute Asthma Exacerbations

Abstract: PurposeProlonged recovery time of pulmonary function after an asthma exacerbation is a significant burden on asthmatics, and management of these patients needs to be improved. The aim of this study was to evaluate factors associated with a longer recovery time of pulmonary function among asthmatic patients hospitalized due to a severe asthma exacerbation.MethodsWe retrospectively reviewed the medical records of 89 patients who were admitted for the management of acute asthma exacerbations. The recovery time of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
(45 reference statements)
1
3
0
Order By: Relevance
“…In our study, the CAP incidence in patients hospitalized with AEs was similar to a Korean (20.2%) study, 30 higher than the studies of Japanese (13.6%) 9 and Italian (7%) 11 populations, and lower than that found in Taiwan, China (30%) 13 . In contrast, the incidence of pneumonia in patients admitted to the intensive care unit (ICU) for severe AEs was only 16.8% in a multicenter retrospective cohort study in the United States 10 .…”
Section: Discussionsupporting
confidence: 89%
“…In our study, the CAP incidence in patients hospitalized with AEs was similar to a Korean (20.2%) study, 30 higher than the studies of Japanese (13.6%) 9 and Italian (7%) 11 populations, and lower than that found in Taiwan, China (30%) 13 . In contrast, the incidence of pneumonia in patients admitted to the intensive care unit (ICU) for severe AEs was only 16.8% in a multicenter retrospective cohort study in the United States 10 .…”
Section: Discussionsupporting
confidence: 89%
“…In detail, patients with a severe asthma exacerbation present a prolonged recovery period. The recovery time and the responsiveness to the treatment are variable here (18). A prolonged recovery may be associated with decreased prognosis and increased morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the asthmatic patients have rare or intermittent exacerbations; however, there is evidence that a subset of asthmatics is ‘exacerbation-prone’ 18 Several epidemiologic studies have reported a strong correlation between FEV1 and the risk of asthma exacerbation. 19 20 21 Acute severe exacerbations in susceptible asthmatics activate pathways of inflammation and remodeling, resulting in the deterioration of lung function. Accelerated loss of lung function in turn increases the risk of exacerbation, resulting in a vicious cycle and the exacerbation-prone phenotype.…”
Section: Discussionmentioning
confidence: 99%